Evaluation of Work Station and Working Posture on Welding Section Review of Ergonomic Factors in Metal SME Road Court Medan - EL-Matury, Herlina J. (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Various risks influencing a worker’s life must be anticipated by synchronizing the worker, work process, and work environment through an ergonomic approach. This study aims at evaluating the synchronization between work station and work posture and recommending the improvement of work station and facilities in the attempt to minimize the complaint of pain caused by their working. The evaluation was conducted by means of a survey method at the UKM Logam (a small business in metal industrial construction) on Jalan Mahkamah Medan with samples of 10 workers working in the welding section. The taking of workers’ anthropometric is an indicator in evaluating the synchronization between workers and work station which is supported by observing the result of the study reveals that there is no working facility in the welding section that the workers do not feel comfortable while working. In addition, the work posture including work attitude is not ergonomically formed that which makes several parts of the worker’s body tired and painful. In the body map questioners, the pain felt by the workers is dominantly found in the area of neck, shoulder, back, waist and calves. For this purpose, the work station needs improvement by setting the position of equipment and machine within the worker’s reach, 75.6 cm (5-th percentile). The benchwork should be adjustable to the height of 92 cm, 95 cm, and 98 cm. The stool (dengklek) should have a height of 14 cm.Berbagai risiko yang mempengaruhi kehidupan pekerja harus diantisipasi dengan menyelaraskan pekerja, proses kerja, dan lingkungan kerja melalui pendekatan ergonomis. Penelitian ini bertujuan untuk mengevaluasi sinkronisasi antara stasiun kerja dan postur kerja dan merekomendasikan perbaikan stasiun kerja dan fasilitas dalam upaya meminimalkan keluhan nyeri yang disebabkan oleh pekerjaan mereka. Evaluasi dilakukan dengan metode survey pada UKM Logam di jalan Mahkamah Medan dengan sampel 10 orang pekerja yang bekerja di bagian pengelasan. Pengambilan antropometri pekerja merupakan salah satu indikator dalam menilai sinkronisasi antara pekerja dengan stasiun kerja yang didukung dengan observasi hasil studi mengungkapkan bahwa tidak ada fasilitas kerja di bagian pengelasan sehingga pekerja tidak merasa nyaman saat bekerja. Selain itu, postur kerja termasuk sikap kerja tidak terbentuk secara ergonomis sehingga membuat beberapa bagian tubuh pekerja lelah dan nyeri. Pada kuesioner body map, nyeri yang dirasakan oleh pekerja dominan ditemukan di daerah leher, bahu, punggung, pinggang dan betis. Untuk itu stasiun kerja perlu diperbaiki dengan mengatur posisi peralatan dan mesin dalam jangkauan pekerja, 75,6 cm (persentil ke-5). Pekerjaan bangku harus disesuaikan dengan ketinggian 92 cm, 95 cm, dan 98 cm. Kotoran (dengklek) harus memiliki tinggi 14 cm.